Proceedings of the 3rd International Conference on Accounting, Management and Economics 2018 (ICAME 2018) 2019
DOI: 10.2991/icame-18.2019.68
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Empowerment, Innovative Work Behavior and Job Satisfaction

Abstract: Psychological empowerment at work contributes to higher individual's performance which eventually facilitates institution to accomplish excellent services and performance. Few studies have examined the specific relationships between these three constructs especially in higher education sector. The aim of this study is to see to what extent psychological empowerment and innovative work behavior affect job satisfaction. From 250 respondents and using SEM AMOS as the analytical tool, the results confirm that psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
4
16
1
Order By: Relevance
“…This result supports the study from Ibrahim et al (2015) and Nasir et al (2019) who found that innovative work behavior has a significant influence on job satisfaction.…”
Section: The Influence Of Innovative Work Behavior On Job Satisfactionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result supports the study from Ibrahim et al (2015) and Nasir et al (2019) who found that innovative work behavior has a significant influence on job satisfaction.…”
Section: The Influence Of Innovative Work Behavior On Job Satisfactionsupporting
confidence: 91%
“…Innovative work behavior can be demonstrated by the competence owned by a person in completing the tasks he is assigned to. When completing the task, he will include a number of innovative ideas, hence he will feel satisfied at work (Nasir, Halimatussakdiah, & Suryani, 2019).The desire and ability of employees to innovate ensures the flow of innovation within the organization (Yesil & Hurlak, 2013). Therefore, many researchers and studies believe in the importance of innovative behavior in the workplace in building organizational performance and survival (Suseno et al, 2019).…”
Section: The Influence Of Innovative Work Behavior On Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizational researchers and practitioners have identified psychological empowerment as a construct that deserves critical attention. The empowerment process also needs support from the leadership because if there is no support from the leadership, cultural change needs to be difficult and empowerment can be said to be impossible to develop EM-2022-4197 (Nasir et al, 2018). The existence of psychological empowerment is one of the elements that shape the innovation process in the workplace (Prabowo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%